2014
DOI: 10.1016/j.jocn.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Repeated neurovascular imaging in subarachnoid hemorrhage when initial studies are negative

Abstract: Approximately 15% of patients with non-traumatic subarachnoid hemorrhage have no causative lesion identified on their initial angiogram. We present two patients with non-traumatic subarachnoid hemorrhage with negative initial angiograms that were subsequently found to have small basilar perforator aneurysms on delayed neurovascular imaging. We discuss the possible mechanisms for false negative diagnostic cerebral angiograms. These patients support the current standard of care with repeat angiography in cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Based on clinical suspicion, negative results of these 2 studies are sometimes investigated with further neurovascular imaging to increase diagnostic yield. 3,27 Patients in this series had all had negative initial neurovascular imaging studies, although the variability of subsequent follow-up studies performed is a potential confounding factor. We feel that all patients represented in this series represent true nonaneurysmal hemorrhage, as was determined during the time of the initial hospitalization according to this protocol, augmented by any delayed outpatient imaging studies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Based on clinical suspicion, negative results of these 2 studies are sometimes investigated with further neurovascular imaging to increase diagnostic yield. 3,27 Patients in this series had all had negative initial neurovascular imaging studies, although the variability of subsequent follow-up studies performed is a potential confounding factor. We feel that all patients represented in this series represent true nonaneurysmal hemorrhage, as was determined during the time of the initial hospitalization according to this protocol, augmented by any delayed outpatient imaging studies.…”
Section: Discussionmentioning
confidence: 94%
“…Repeated neurovascular imaging is often performed to identify an aneurysmal source that may not have been apparent on initial studies. 2,3 When spontaneous SAH is seen without an aneurysmal source, hemorrhage patterns can be dichotomized into either the perimesencephalic pattern (figure 1), 4 where blood is confined mainly to the basal cisterns surrounding the midbrain, or diffuse (figure 2), where blood extends into the distal Sylvian or interhemispheric fissures. Although nonaneurysmal hemorrhage has typically been associated with a benign course, 5-8 recent evidence has suggested that hydrocephalus, vasospasm, and stroke can all occur.…”
mentioning
confidence: 99%
“…The main aetio-logy of spontaneous SAH is a ruptured cerebral aneurysm. However, in about 15% of cases the source of bleeding cannot be determined [ 8 ], leading to a condition known as idiopathic SAH.…”
Section: Introductionmentioning
confidence: 99%